Composition of stingless bee honey: Setting quality standards - Souza, Bruno; Roubik, David; Barth, Ortrud; Heard, Tim; EnrÍquez, Eunice; Carvalho, Carlos; Villas-Bôas, Jerônimo [UNESP]; Marchini, Luis; Locatelli, Jean; Persano-Oddo, Livia; Almeida-Muradian, Ligia; Bogdanov, SteFan; et al. (My University, 2006)
Compositional data from 152 stingless bee (Meliponini) honey samples were compiled from studies since 1964, and evaluated to propose a quality standard for this product. Since stingless bee honey has a different composition than Apis mellifera honey, some physicochemical parameters are presented according to stingless bee species. The entomological origin of the honey was known for 17 species of Meliponini from Brazil, one from Costa Rica, six from Mexico, 27 from Panama, one from Surinam, two from Trinidad & Tobago, and seven from Venezuela, most from the genus Melipona. The results varied as follows: moisture (19.9-41.9g/100g), pH (3.15-4.66), free acidity (5.9-109.0meq/Kg), ash (0.01-1.18g/100g), diastase activity (0.9-23.0DN), electrical conductivity (0.49-8.77mS/cm), HMF (0.4-78.4mg/Kg), invertase activity (19.8-90.1IU), nitrogen (14.34-144.00mg/100g), reducing sugars (58.0-75.7g/100g) and sucrose (1.1-4.8g/100g). Moisture content of stingless bee honey is generally higher than the 20% maximum established for A. mellifera honey. Guidelines for further contributions would help make the physicochemical database of meliponine honey more objective, in order to use such data to set quality standards. Pollen analysis should be directed towards the recognition of unifloral honeys produced by stingless bees, in order to obtain standard products from botanical species. A honey quality control campaign directed to both stingless beekeepers and stingless bee honey hunters is needed, as is harmonization of analytical methods. © 2007 Asociación Interciencia.
Keywords: Honey; Pollen analysis; Quality criteria; Stingless bee honey; Apis mellifera; Melipona; Meliponinae